Probiotic Yogurt Culture Bifidobacterium Animalis Subsp. Lactis BB-12 and Lactobacillus Acidophilus LA-5 Modulate the Cytokine Secretion by Peripheral Blood Mononuclear Cells from Patients with Ulcerative Colitis - Sheikhi, A.; Shakerian, M.; Giti, H.; Baghaeifar, M.; Jafarzadeh, A.; Ghaed, V.; Heibor, M. R.; Baharifar, N.; Dadafarin, Z.; Bashirpour, G. (Drug Research, 2016)
Background: There are some evidences for the immunomodulation disorders in the response to intestinal microbiota in inflammatory bowel disease. Yogurt is a fermented milk product made with a starter culture consisting of different probiotics which could be colonized in intestine. However, the role of probiotics in the aetiopathogenesis of ulcerative colitis (UC) has not been clarified. To determine how the immune system responds to these bacteria this study was planned.Methods: Bifidobacterium lactis BB-12 (B. lactis) and Lactobacillus acidophilus LA-5 (L. acidophilus) were cultivated on MRS broth. PBMCs of 36 UC patients were separated by Ficoll-Hypaque centrifugation and co-cultured with different concentrations of UV killed bacteria in RPMI-1 640 plus 10% FCS for 48/72 h. IL-10, TGF-β, IFN-γ and TNF-α were measured in supernatant of PBMCs by ELISA.Results: Both bacteria significantly augmented IL-10, TGF-β, IFN-γ and TNF-α compared to control (p<0.001). The secretion levels of IL-10 and TGF-β by B. lactis- compared to L. acidophilus-stimulated PBMCs were significantly higher (p<0.05, p<0.01 respectively). The secretion levels of TNF-α and IFN-γ by PBMCs after 72 h were significantly lower compared to 48 h stimulation by B. lactis (p<0.001, p<0.035 respectively).Conclusion: These data show that both probiotics may trigger the pro- and anti-inflammatory immune response of UC patients. It seems that IL-10/TGF-β uprising by B. lactis could be the reason of TNF-α/IFN-γ reduction. Therefore albeit B. lactis still stimulates the effector Th cells but because of more stimulatory effect on Tregs, it could be a good potential therapeutic candidate for further investigation.
Keywords: immunomodulation; ulcerative colitis; bifidobacterium lactis; lactobacillus acidophilus; probiotics